Industrial Land Use Agreement between PT. SIER with Tenant Judging from the Legal Terms of the Agreement - Arisandy, Achmad Yovan; Purwaningsih, Sri Budi (Indonesian Journal of Public Policy Review, 2020)
The Industrial Land Use Agreement between PT SIER and the Tenants has been going on since the 1980s. According to PP No. 40 of 1996, the tenants have a Building Use Right over the Management Right for 30 years and can be extended for another 20 years. This study aims to determine whether the agreement is in accordance with the legal terms of the agreement because there are new provisions to extend its rights. This type of research is normative, the object of which lies in the principles applied in the contract and theoretical aspects of land law as well as normative studies related to the use of land on management rights. The results of the research from this agreement when viewed from Article 1320 of the Civil Code have actually been legally fulfilled as long as there is no element of coercion from the Tenant who pays the income. As well as the existence of a strong legal basis from PT SIER to make new provisions regarding income money to extend the Right to Build